Enhancing Medication History Accuracy in a Tertiary Hospital: Pharmacist-Led Counseling With Nationwide Medication History Sharing Program Versus Conventional Methods - Hyunwoo Chae; Subin Yoon; Soyoung Park; A Jeong Kim; Kyu-Nam Heo; Yookyung Kim; Jeong Yeon Seok; Sung Hwan Kim; Taeyoung Yun; Ji Hyeon Park; Yoon Sook Cho; Young Tae Kim; et al. (International Journal of Clinical Practice)
Conclusions: Pharmacist-led BPMH significantly improved medication history accuracy compared to conventional methods, which had inaccuracies in over 70%. It is important to be careful when obtaining BPMH for older adults, particularly those with complex medication regimens, nonoral medications, or PRN medications, to enhance patient safety and reduce medication-related risks.